2018
DOI: 10.3389/fimmu.2018.00795
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal on the Potential Ability of Human Neutrophils to Express and Produce IL-17 Family Members In Vitro: Failure to Reproducibly Detect It

Abstract: Neutrophils are known to perform a series of effector functions that are crucial for the innate and adaptive responses, including the synthesis and secretion of a variety of cytokines. In light of the controversial data in the literature, the main objective of this study was to more in-depth reevaluate the capacity of human neutrophils to express and produce cytokines of the IL-17 family in vitro. By reverse transcription quantitative real-time PCR, protein measurement via commercial ELISA, immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 84 publications
5
43
2
Order By: Relevance
“…We could also fully confirm and extend the observations concerning the AF‐317‐NA antibody . Accordingly, by IHC staining using AF‐317‐NA antibody we detected IL‐17A + ‐neutrophils not only in skin sections of psoriasis patients, but also in cytospin slides of peripheral cells isolated from healthy donors and incubated for 3 hours with or without R848 . However, whole lysates of the same neutrophil populations displayed major signals at levels of proteins having MW not corresponding to that of IL‐17A when immunoblotted with AF‐317‐NA antibody .…”
Section: The Case Of Il‐17 Expression In Human Neutrophilssupporting
confidence: 74%
See 2 more Smart Citations
“…We could also fully confirm and extend the observations concerning the AF‐317‐NA antibody . Accordingly, by IHC staining using AF‐317‐NA antibody we detected IL‐17A + ‐neutrophils not only in skin sections of psoriasis patients, but also in cytospin slides of peripheral cells isolated from healthy donors and incubated for 3 hours with or without R848 . However, whole lysates of the same neutrophil populations displayed major signals at levels of proteins having MW not corresponding to that of IL‐17A when immunoblotted with AF‐317‐NA antibody .…”
Section: The Case Of Il‐17 Expression In Human Neutrophilssupporting
confidence: 74%
“…Interestingly, we made similar findings in relation to the expression of IL‐17B by human neutrophils . Again, we tested a commercial anti‐IL‐17B antibody (#AF1248) previously shown to detect IL‐17B + ‐neutrophils in synovial membranes of RA patients and in the stroma of colon carcinoma cancer by IHC/IF, as well as by immunoblotting of freshly isolated cells .…”
Section: The Case Of Il‐17 Expression In Human Neutrophilssupporting
confidence: 64%
See 1 more Smart Citation
“…More recently, human neutrophils (whose purity was not stated) were shown to express IL‐23 (presumably IL‐23p19) mRNA, as well as to produce very elevated levels of IL‐23 protein, when infected with Mycobacterium tuberculosis H37Rv or when incubated with either LPS or Pam3CSK4 (a TLR2 agonist) . However, in these experiments the infected neutrophils were also reported to express IL‐17, which, according to our previous work, does not occur. Finally, immunofluorescence and flow cytometry analyses revealed that, in patients with castration‐resistant prostate cancer (CRPC), tumor‐infiltrating myeloid‐derived suppressor cells with the neutrophil phenotype (CD11b + CD33 + CD15 + cells, polymorphonuclear cell‐myeloid‐derived suppressor cells) express IL‐23 …”
Section: Discussionmentioning
confidence: 63%
“…Although IL‐17A production has historically been conceptualized in terms of upstream IL‐23 signaling, it is increasingly evident that IL‐17 family production, especially by innate cells, may be independent of IL‐23, but the in vivo mechanisms are not clear . The concept that neutrophils are also a IL‐17–expressing cell is highly controversial and heavily debated, and at this time, there are no data on the immunobiology of entheseal‐resident neutrophils and the cytokines they produce. In humans, cytokine stimuli such as IL‐1β, IL‐6, IL‐21, and/or IL‐23 can drive IL‐17 production .…”
Section: The Il‐23 Cytokinementioning
confidence: 99%